Pengembangan Aplikasi Mobile untuk Pasien Telkomedika dengan Tipe Kepribadian Influence Menggunakan Metode Design Thinking - Mohamad, Ilham Syarief Roem; Perdana, Ilham; Nuraliza, Hilda (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The digitalization of healthcare services has transformed the Indonesian healthcare business, making health services more accessible. Digitalization improves medical services and outcomes. However, the academic community frequently encounters challenges when using Telkomedika services or getting information fast. As a result, further efforts are needed to ensure that the platform provides a seamless and efficient user experience. One area that can be improved is the user interface. A more engaging design can help users navigate the site more easily. This incorporates a cleaner, clearer layout and a responsive design, allowing consumers to use all Telkomedika functions with ease. This study used a design thinking technique to develop the user interface and experience for the Telkomedika application, taking into account the Influence personality type. According to the DISC model, this type identifies people who are outgoing, extroverted, and prefer broad social circles. According to the findings, this technique efficiently meets patients' demands and preferences, resulting in increased comfort and pleasure.